2019
DOI: 10.1101/639054
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mouse and human microglial phenotypes in Alzheimer’s disease are controlled by amyloid plaque phagocytosis through Hif1α

Abstract: The important role of microglia, the brain’s resident immune cells, in Alzheimer’s disease (AD) is now well recognized, however their molecular and functional diversity and underlying mechanisms still remain controversial. To transcriptionally and functionally characterize the diversity of microglia in AD and aging, we isolated the amyloid plaque-containing (XO4+) and non-containing (XO4−) microglia from an AD mouse model. Transcriptomics analysis unveiled independent transcriptional trajectories in ageing and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 106 publications
(130 reference statements)
0
11
0
Order By: Relevance
“…The majority of these markers were from microglia (Supplementary Table 5). To further validate these findings, we analyzed whether these markers were increased at both the transcript and protein levels in acutely isolated microglia from AD mouse models 48,49 . The top 30 most differentially abundant microglial transcripts corresponding to proteins in the M4 module were found to be heavily biased toward an anti-inflammatory phenotype (Figure 6D, Supplementary Table 5).…”
Section: Analyzed By a Different Mass Spectrometry-based Quantificatimentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of these markers were from microglia (Supplementary Table 5). To further validate these findings, we analyzed whether these markers were increased at both the transcript and protein levels in acutely isolated microglia from AD mouse models 48,49 . The top 30 most differentially abundant microglial transcripts corresponding to proteins in the M4 module were found to be heavily biased toward an anti-inflammatory phenotype (Figure 6D, Supplementary Table 5).…”
Section: Analyzed By a Different Mass Spectrometry-based Quantificatimentioning
confidence: 99%
“…The top 30 most differentially abundant microglial transcripts corresponding to proteins in the M4 module were found to be heavily biased toward an anti-inflammatory phenotype (Figure 6D, Supplementary Table 5). Furthermore, many of the disease-associated M4 microglial protein markers were found to be increased in microglia undergoing active amyloid plaque phagocytosis ( Supplementary Figure 7, Supplementary Table 5) 49 . In summary, we found that the M4 astrocyte/microglial metabolism module was enriched in AD genetic risk factors, and that microglia cell type markers within M4 appeared to be biased towards a protective anti-inflammatory, rather than a deleterious proinflammatory, microglial phenotype.…”
Section: Analyzed By a Different Mass Spectrometry-based Quantificatimentioning
confidence: 99%
See 1 more Smart Citation
“…Activation of the DAM program, which is TREM2 dependent, has been predicted computationally to rely on four transcription factors: basichelix-loop-helix family member E40 (BHLHE40), RXR gamma (RXRG), hypoxia-inducible factor 1-alpha (HIF1a), and microphthalmia-associated transcription factor (MITF). Among these, HIF1a expression is increased in DAMs in a TREM2-dependent manner in a 5xFAD AD mouse model (Keren-Shaul et al, 2017;Ulland et al, 2017), and a recent preprint showed that HIF1a controls microglial ability to engulf plaques, which entails induction of the DAM phenotype in an AD mouse model (Grubman et al, 2019b). Further experiments with human embryonic stem cell (ESC)-derived microglia-like cells in vitro showed that HIF1a promotes this transition via myeloid differentiation primary response 88 (MyD88) and mTor (Grubman et al, 2019b).…”
Section: Llmentioning
confidence: 99%
“…For the bulk RNAseq of the iTSC and iTSC-differentiated cells, RNA-seq was performed with a multiplexing approach, using an 8 bp sample index 48 and a 10 bp unique molecular identifier (UMI) were added during initial poly(A) priming and pooled samples were amplified using a templateswitching oligonucleotide. The Illumina P5 (5' AAT GAT ACG GCG ACC ACC GA 3') and P7 (5' CAA GCA GAA GAC GGC ATA CGA GAT 3') sequences were added by PCR and Nextera transposase, respectively.…”
Section: Rna-seq For Characterization Of Itscs and Itsc-differentiatementioning
confidence: 99%